Lithuanian First Independence Period Book Binder Zigmas Malašauskas - Taukinaitytė-Narbutienė, Rūta (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]Zigmas Malašauskas is a little known interwar period bookbinder who lived and worked in Kaunas in the 1930s. After collecting and evaluating archival sources and publications, his extraordinary ambitions and active public educational activities with the purpose to promote his profession, the need and understanding of artistic bindings, to raise the level of craft and the qualification of his colleagues bookbinders were revealed. His lively articles in the press were dedicated both to the general public (a consumer) and masters of bookbindery. Also, letters to some public authorities and public organizations that deal with various, often naive but reasoned requests or proposals, reveal the real intention to seek the attention, co-operation and support of the state, and to prove the importance of this kind of art.Although his efforts did not received response and were not acomplished, his articles probably influenced the development of the book lovers community of that time. And most important, since he was the only one that has been writing so much on bookbindery, he left many reliable data (verified by other sources too) for a nowadays researcher about bookbindery and its problems, masters and prices, stastistics and estimations, working methods, learning resources, acquired knowledge, skills and tools.The research did not lead to identification of any books bound by this bookbinder. Still there are left many unknown biographical facts, therefore it is expected that this article will encourage or facilitate further research of this person’s life and work, to discover and identify his bindings.
Keywords: Zigmas Malašauskas, bookbinding in 1918–1940, heritage of bookbinding